2008
DOI: 10.1143/jjap.47.8973
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Electrical Properties of 1,8-Bis(3-hydroxypropylamino) and 1-(3-Hydroxypropylamino)–9,10-anthraquinone Films

Abstract: The method of computer aided vacancy migration analysis has been developed to predict the stress induced voiding (SiV) reliability. In this method, distribution of hydrostatic stress was calculated by the finite element analysis (FEA), and vacancy concentration distribution was calculated by the finite difference analysis (FDA). In this paper, SiV acceleration tests were conducted in various widths of Cu lines in organic ultralow-k dielectric (Cu/Ta/ULK/SiCN) or silicon oxide dielectric (Cu/Ta/SiO 2 /SiCN) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…It has been stated previously that the molecular arrangement changes upon reduction, aggregates become smaller, and the smooth layered structure is deformed. Moreover, in a previous study, it was found that the increase in the crystallite size increases the conductivity . Thus, it is thought that both the change in the conjugation of the AQ ring and the transformation of the aggregate morphology have a role in this significant conductivity decrease.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…It has been stated previously that the molecular arrangement changes upon reduction, aggregates become smaller, and the smooth layered structure is deformed. Moreover, in a previous study, it was found that the increase in the crystallite size increases the conductivity . Thus, it is thought that both the change in the conjugation of the AQ ring and the transformation of the aggregate morphology have a role in this significant conductivity decrease.…”
Section: Resultsmentioning
confidence: 91%
“…Moreover, in a previous study, it was found that the increase in the crystallite size increases the conductivity. 56 Thus, it is thought that both the change in the conjugation of the AQ ring and the transformation of the aggregate morphology have a role in this significant conductivity decrease. This decrease is such that the aggregates switch from significantly conductive to almost insulative.…”
Section: ■ Results and Discussionmentioning
confidence: 99%